BSAVA Congress Proceedings 2019 2019
DOI: 10.22233/9781910443699.84.1
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, treatment and outcome of fractures in pet rabbits (Oryctolagus cuniculus)

Abstract: To identify the incidence, aetiology, characteristics, assessment, management and outcome of bone fractures in rabbits presenting to a single institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…The percentage of treatments with a positive outcome was comparable to the results of a previous report by Garcia-Pertierra et al, 9 who found a positive therapy outcome in 76.9% of all treated rabbits. However, Sasai et al 7 found a higher number of positive therapy outcomes (86.0%).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The percentage of treatments with a positive outcome was comparable to the results of a previous report by Garcia-Pertierra et al, 9 who found a positive therapy outcome in 76.9% of all treated rabbits. However, Sasai et al 7 found a higher number of positive therapy outcomes (86.0%).…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of limb bone fractures was comparable to previous studies examining limb fracture occurrence in rabbits, 7,9 cats and dogs. [22][23][24] The percentage of open fractures was similar to that in a study by Garcia-Pertierra et al, 9 but lower than that reported by Sasai et al 7 Incorrect handling by the animal owners as well as the rabbits' natural behaviour, including powerful and fast limb movements together with comparably light bones accounting for only 6%-8% of total body mass, 3,25 predispose pet rabbits to limb fractures. Depending on the housing form, regularity of animal control by the owners and individual signs of pain, 26,27 an early recognition of limb fractures might be difficult.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations